(3GdQhVI hGdZOjQ aj HjGf eG JMJGLg GdBjGJ GdTQYjI ef GdJaSjQs - (3YR GdOjf eMeO Hf GdgGOj Hf JGL GdOjf,J (B720 (3g` s ((3eMeO YdG s)
(3ChdgG (B:s
(3GdMeO ddg GdQMef GdQMje GdCRdi GdbOje CeG HYO aEfi fXQJ Edi GdbQBf eTJedkG Ydi LejY afhf GdYde ef YOd hJhMjO EdG Cf WGdH GdaGFOI ai GdBjGJ GdeNJUI HGdMdGd dGjbY efgG Ydi GdbUO s
(3BNQgG (B:s
(3bGd (B: (3GdeVeVI hGdESJfTGb ef GdhVhA dGJbHd GdUdGI EdG HgeG Je GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ YfGhjjf GdaUhd hGdahGJM HGdSejc s
(3HBNQgG HNW MOjK JQLeI ddeDda hagQS s
(3bQf GdfSN (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs